Diversity of phytoplankton at Langkawi Island, Malaysia - A, Salleh; Wakid S, Ahmad; Bahnan I, Shah; Rahman K. A, Abdul; S, Nasrodin (Malaysian Journal of Science, 2005)
A study on the biodiversity of phytoplankton was carried out at Langkawi Island for seven days from 4 to 10 April 2004. Thirteen samplings were done at selected sites, including Sungai Kilim, Sungai Banja, Sungai Itau, Tanjung Rhu, Sungai Belanga Pecah, Sungai Air Hangat, Sungai Padang Lalang and Sungai Kisap . A total of 106 species of phytoplankton from 29 genera were recorded. Chaetoceros constrictum, Chaetoceros laeve, Bacteriastrum varians, Ditylium sol, Ditylium brightwelli, Rhizosolenia alata var gracillima, Thalassiothrix nitzschioides and Thalassiothrix frauenfeldii were major phytoplankton species in this island area.